Service quality in Lanai Kijang based on the perception of the international guest / Shariha Roseley - Roseley, Shariha (2011)
As stated in the introduction on BNM, it is the regulatory body that basically controlled and preserved the sound financial health of the country. Therefore, in performing the functions that have been stated above it got the supports of 37 departments in BNM. So it involves dealing with many client or support partner whether locally or overseas in order to ensure they serve the country well. Therefore, one of the departments in charged in handling the facilities of BNM is called Sasana Lanai Kijang Management Office or SLKMO. The department basically took care of the facilities that would be Lanai Kijang and the next facilities that are expected to be completed by the end of the year called Sasana Kijang. Both facilities were nearby to BNM therefore it facilitated the usage of Lanai to fit the purpose that it was supposed to serve meanwhile Sasana still building in progress. The name of Lanai Kijang originated from the two words from Malay language that would be Lanai and Kijang. Which Lanai mean a verandah or a patio which reflect a place to learned in the old Malay community while Kijang mean raindeer which also used as the distinctive symbol in BNM’s logo and synonymous with its history and accomplishment. Therefore the merger of both word bring out Lanai Kijang which BNM used to named their facilities.